PENGARUH MANAJEMEN TALENTA DAN WORKFORCE AGILITY TERHADAP KINERJA KARYAWAN PT. HUTAN MAKMUR INDONESIA - Aditya Yusuf; Ika Indriasari; Violinda, Qristin (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
This study aims to determine the Effect of Talent Management and Workforce Agility on Employee Performance at PT. Indonesian Prosperous Forest (HMI). The research population is all employees of PT. Hutan Makmur Indonesia (HMI) as many as 300 people, the sample that has been determined in this study is 93 employees using the Non-probability sampling technique with the purposive sampling method. Data analysis in this study used the SPSS 24 program. Testing the hypothesis with a multiple linear regression approach. The results of the analysis and discussion show that the variables have a partial effect, namely; Talent Management has a positive and significant effect on Employee Performance, Workforce Agility has a positive and significant effect on Employee Performance, simultaneously Talent Management and Workforce Agility have a positive and significant effect on Employee Performance at PT. Indonesia's Prosperous Forest